2020
DOI: 10.2147/tcrm.s261303
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hematotoxic Manifestations and Management of Green Pit Viper Bites in Thailand</p>

Abstract: Introduction: Green pit vipers (GPV) are widely distributed throughout Thailand and are responsible for significant morbidity. The primary objective of this study was to characterize clinical presentations and treatment methods for GPV bites. The secondary objective was to demonstrate the earliest and latest onset of hematotoxicity. Methods: GPV bites reported to the Ramathibodi Poison Center between July 1, 2016, and June 30, 2018, were analyzed. Results: There were 288 GPV cases within the study period. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…Respiratory symptoms were the second most frequent clinical manifestation of EARs. Both findings are consistent with previous studies of QSMI antivenoms [ 3 , 4 , 5 , 17 , 18 , 43 ]. Severe reactions occurred with an EAR rate of 2.6% and were mainly characterized by hypotension, which is the symptom most often reported in previous studies [ 5 , 11 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Respiratory symptoms were the second most frequent clinical manifestation of EARs. Both findings are consistent with previous studies of QSMI antivenoms [ 3 , 4 , 5 , 17 , 18 , 43 ]. Severe reactions occurred with an EAR rate of 2.6% and were mainly characterized by hypotension, which is the symptom most often reported in previous studies [ 5 , 11 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Epidemiological data reported before 2015 indicated that most venomous bites in Thailand were due to MPV [ 6 ]. However, our findings, in addition to those of studies from 2016 onward, demonstrate a changing trend, with Trimeresurus species or GPV being the most common type [ 3 , 6 ]. A higher risk of snakebites was found in adult males than females, and the peak incidence was in young adults.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In some provinces of Vietnam (eg Lam Dong Province) it is the most frequent cause of snakebite. 9 , 10 Trimeresurus mucrosquamatus has a wide geographic distribution. It causes a serious medical threat to people because of their overlapping habitats with areas of human activities, frequenting human dwellings in pursuit of prey, and inflicting severe envenomation.…”
Section: Discussionmentioning
confidence: 99%